N6-methyladenosine RNA methylation: From regulatory mechanisms to potential clinical applications - Li, Peipei; Wang, Yuntao; Sun, Yiwen; Jiang, Sanjie; Li, Jingjing (Frontiers in Cell and Developmental Biology, 2022)
Epitranscriptomics has emerged as another level of epigenetic regulation similar to DNA and histone modifications. N6-methyladenosine (m6A) is one of the most prevalent and abundant posttranscriptional modifications, widely distributed in many biological species. The level of N6-methyladenosine RNA methylation is dynamically and reversibly regulated by distinct effectors including methyltransferases, demethylases, histone modification and metabolites. In addition, N6-methyladenosine RNA methylation is involved in multiple RNA metabolism pathways, such as splicing, localization, translation efficiency, stability and degradation, ultimately affecting various pathological processes, especially the oncogenic and tumor-suppressing activities. Recent studies also reveal that N6-methyladenosine modification exerts the function in immune cells and tumor immunity. In this review, we mainly focus on the regulatory mechanisms of N6-methyladenosine RNA methylation, the techniques for detecting N6-methyladenosine methylation, the role of N6-methyladenosine modification in cancer and other diseases, and the potential clinical applications.